Tests on the Accuracy and Scalability of the Full-Potential DFT Method Based on Multiple Scattering Theory - Cao, Peiyu; Fang, Jun; Gao, Xingyu; Tian, Fuyang; Song, Haifeng (Frontiers in Chemistry, 2020)
We evaluate a low-order scaling full-potential DFT method based on the multiple scattering theory (MST) code MuST which is released online (https://github.com/mstsuite/MuST) very recently. First, we investigate the accuracy by calculating structural properties of typical body-centered cubic (BCC) metals (V, Nb and Mo), and find that the treatment of core states plays an important role in predicting equation of state (EOS). It is shown that the calculated lattice parameters, bulk moduli and elastic constants agree with those obtained from VASP, WIEN2k, EMTO and Elk codes. Second, we test the locally self-consistent multiple scattering (LSMS) mode which achieves low-scaling by neglecting the multiple scattering processes beyond a cut-off radius. In the case of metal Nb, the accuracy of 0.5 mRy/atom can be achieved with the cut-off radius of 20 Bohr even though the small deformation is applied to the lattice. Despite it exhibits linear scaling in computing the valence states based on MST, the overall procedure shows about $\mathcal{O}(N^{1.6})$ scaling since updating Coulomb potential scales almost as $\mathcal{O}(N^2)$. It can be expected that MuST will provide a reliable and accessible way to large-scale first-principles simulations of metals and alloys.